2021
DOI: 10.3390/vaccines9040336
|View full text |Cite
|
Sign up to set email alerts
|

HPV Type-Specific Prevalence a Decade after the Implementation of the Vaccination Program: Results from a Pilot Study

Abstract: Human papillomavirus infection is a cause of the development of invasive cervical cancer. Three types of vaccine are currently available to prevent precancerous/cancerous lesions due to persistent infection, which is supported mainly by 7 different high-risk genotypes. The aim of this pilot study was to acquire preliminary data on type-specific prevalence 10 years after the implementation of the HPV vaccination program in Italy, in order to subsequently plan appropriate observational studies in the Italian pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…One study examining 1300 HPV-associated cancers [ 44 ] suggested infection by different HPV types is unrelated and independent. However, overall evidence, including data from randomised controlled trials, cohort studies and mathematical models, have suggested HPV types are synergistic, meaning any vaccine which decreases the prevalence of vaccine-types will lead to a reduction in infections by other types [ 38 , 39 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…One study examining 1300 HPV-associated cancers [ 44 ] suggested infection by different HPV types is unrelated and independent. However, overall evidence, including data from randomised controlled trials, cohort studies and mathematical models, have suggested HPV types are synergistic, meaning any vaccine which decreases the prevalence of vaccine-types will lead to a reduction in infections by other types [ 38 , 39 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Real-life evidence of HPV vaccine effectiveness has become increasingly evident, especially in females vaccinated before sexual exposure to HPV [ 43 ]. In our study, the modeling analysis, adjusting for 4vHPV immunization before initiating sexual activity, showed that cases were 32% less likely to have higher antibody titers than controls (OR = 1.47, p = 0.08).…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated according to the data reported by other studies in Iran 12 - 14 and measured with the following equation considering a 95% confidence interval with an absolute precision of ± 5%. 15 …”
Section: Methodsmentioning
confidence: 99%